National Identities and Travel in Victorian Britain - Morgan, M. author. aut Link
X, 271 p.
Keywords: This book explores components of national identity in Victorian Britain by analyzing travel literature. It draws on published and unpublished travel journals by middle-class men and women from England, Scotland, and Wales who toured the Continent and/or Britain. The main aim is to illustrate both the contexts that inspired the various collective identities of Britishness, Englishness, Scotsness, and Welshness, as well as the qualities Victorian men and women had in mind when they used such terms to identify and imagine themselves collectively.